Morphological description and DNA barcodes of shallow-water Tetractinellida (Porifera: Demospongiae) from Bocas del Toro, Panama, with description of a new species - Cárdenas, Paco; Menegola, Carla; Rapp, Hans Tore; Díaz, Maria Cristina (Zootaxa, 2009)
Tetractinellida Marshall 1876 [Borchiellini et al. 2004] comprises the Orders Spirophorida and Astrophorida. A surveyof their diversity in the Bocas del Toro archipelago (Panama) was conducted. A total of ten species of Tetractinellidawere encountered: Cinachyrella alloclada, Cinachyrella apion, Cinachyrella kuekenthali, Ecionemia megastylifera,Stelletta fibrosa, Stelletta sp., Stryphnus raratriaenus sp. nov., Erylus formosus, Geodia gibberosa and Geodiapapyracea. Five of these species are new to the Atlantic sponge fauna of Panama, one of which is new to science.Stryphnus raratriaenus sp. nov. is very similar to Caribbean Asteropus species but it possesses triaenes. It is the firstspecies of this genus in the Caribbean. The description of Ecionemia megastylifera Wintermann–Kilian & Kilian, 1984 ishere revised and the species fully redescribed. A cytochrome c oxidase subunit I (COI) gene partial fragment and/or a 28S ribosomal gene partial fragment (C1–D2 domains) were sequenced for some of the species collected.